EFFECTIVENESS MODEL OF PROVINCIAL FINANCIAL ASSISTANCE IN STRENGTHENING VILLAGE GOVERNMENT CAPACITY: POLICY ANALYSIS IN WEST JAVA - M. Rijal Amirulloh; Hartuti Purnaweni; Agustina Rina Herawati; Budi Puspopriyadi (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
This research analyzes the effectiveness of provincial financial assistance policies in strengthening village government capacity in West Java using a comprehensive approach. While fiscal transfer systems from central government to villages have been extensively studied, the role of provincial governments as fiscal mediators in decentralized systems still requires in-depth examination. This study employs a mixed-methods approach by integrating structural equation modeling analysis of surveys from 200 village governments and thematic analysis of in-depth interviews with 30 strategic stakeholders. The results reveal that provincial financial assistance contributes significantly to improving village government performance through direct pathways (β = 0.35, p < 0.01) and indirect pathways mediated by village administrative capabilities (β = 0.18, p < 0.01). Other important findings indicate that accountability mechanisms serve as positive moderators (β = 0.27, p < 0.01), while community participation levels show no significant moderating effect. Based on resource-based theory and agency theory perspectives, this research identifies complex interactions between fiscal assistance, administrative capabilities, and governance that have not been fully revealed in previous fiscal transfer studies. These findings provide an empirical basis for developing more effective provincial assistance policies through aligning aid with village needs, strengthening apparatus capacity, implementing balanced accountability mechanisms, and empowering transformative leadership at the village level. This research contributes to food security and human resource strengthening by demonstrating how improved village governance capacity enhances local development effectiveness and community welfare outcomes. The contribution of this research provides a foundation for reformulating fiscal relationships between government levels in the context of village autonomy in developing countries.